The Florida Plant Diagnostic Network - Aaron J. Palmateer; Carrie L. Harmon; Amanda Hodges; Natalia Peres; Kuang Ren Chung; Pamela D. Roberts; Lyle Buss; William T. Crow; Jiannong Xin; Robert J. McGovern; James W. Kimbrough; Timur M. Momol (EDIS)
PP-229, a 6-page fact sheet by A.J. Palmateer, C.L. Harmon, A. Hodges, N. Peres, K.R. Chung, P.D. Roberts, L. Buss, W.T.. Crow, J. Xin, R.J. McGovern, J. W. Kimbrough, and M.T. Momol, describes Florida's network of support for the rapid detection, diagnosis, and decision support for pathogens and other pests affecting Florida's agricultural and natural ecosystems. Provides information on diagnostic services, Distance Diagnostic and Identification System (DDIS), First Detector Training, and other services. Published by the UF Plant Pathology Department, April 2006.